2009
DOI: 10.1002/cncy.20043
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid capture 2 human papillomavirus DNA testing for women with atypical squamous cells of undetermined significance papanicolaou results in SurePath and ThinPrep specimens

Abstract: BACKGROUND:Human papillomavirus (HPV) DNA testing using Hybrid Capture 2 assay with ThinPrep Papanicolaou (Pap) collection is the only US Food and Drug Administration‐approved method for the triage of women with atypical squamous cells of undetermined significance (ASCUS). Although SurePath Pap collection has been used for Hybrid Capture 2 HPV DNA testing, clinical validation of this method has been scarce.METHODS:From a cervical cancer‐screening program in Mississippi, we analyzed data from screenings of 8380… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 14 publications
1
7
0
Order By: Relevance
“…Their retrospective study design differed from ours in several aspects: the screening population was larger, and the majority of the subjects were African American or Caucasian; the age range was much greater, but the median age was lower; and the accuracy of HC2 testing could not be calculated because women with negative HC2 results did not undergo biopsy. 29 In conclusion, compared with the ThinPrep method, the SurePath method yielded significantly lower rates of inadequate cytology and inadequate volumes for HC2 with comparable diagnostic accuracies. Researchers and clinicians should contemplate some of the factors we have discussed to optimize the potential of a specific method of LBC preparation for gynecologic specimens, with special consideration for the option of HPV DNA testing on residual specimens.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Their retrospective study design differed from ours in several aspects: the screening population was larger, and the majority of the subjects were African American or Caucasian; the age range was much greater, but the median age was lower; and the accuracy of HC2 testing could not be calculated because women with negative HC2 results did not undergo biopsy. 29 In conclusion, compared with the ThinPrep method, the SurePath method yielded significantly lower rates of inadequate cytology and inadequate volumes for HC2 with comparable diagnostic accuracies. Researchers and clinicians should contemplate some of the factors we have discussed to optimize the potential of a specific method of LBC preparation for gynecologic specimens, with special consideration for the option of HPV DNA testing on residual specimens.…”
Section: Discussionmentioning
confidence: 81%
“…28,29 A study in the United Kingdom concluded that ThinPrep and SurePath had equivalent performances using a variety of predictive values. The study excluded HC2-tested samples that might have been at increased risk for high-grade cervical lesions and their cytology specimens were diagnosed according to UK National Health Service Cancer Screening Program classification guidelines.…”
Section: Discussionmentioning
confidence: 99%
“…25,32 Also, positive and equivocal HC II hrHPVT cohorts had similar rates for overall high-grade dysplasia (CIN2,3, p = .5696). 25,32 Also, positive and equivocal HC II hrHPVT cohorts had similar rates for overall high-grade dysplasia (CIN2,3, p = .5696).…”
Section: Discussionmentioning
confidence: 88%
“…25,36 In contrast, others suggest that the manufacturer's preestablished positive threshold may be too low, and therefore, increasing it may be necessary to resolve these issues. Data in support of the established algorithm may have been influenced by results drawn from the study of a younger population and broad referral of patients with ASC-US cytology to colposcopy irrespective of accompanying hrHPVT result and cervical biopsy.…”
Section: Discussionmentioning
confidence: 99%
“…22 Storage duration and temperature are not reported and such a low sensitivity has not been replicated in other studies. 12,26 Some studies report a lower nucleic acid recovery rate in SurePath TM medium compared to ThinPrepV R medium, and this has been postulated to be due to a higher rate of nucleic acid degradation over time or cross-linking in SurePath TM specimens due to the presence of a low concentration of formalin in the medium. 11,12,[23][24][25] In published reports of hrHPV HC2 testing using ThinPrepV R specimens, the sensitivity of abnormal cytology ranges from 50% to 100% for predicting CIN 2 and above.…”
Section: Discussionmentioning
confidence: 99%